2013
DOI: 10.1016/j.econmod.2013.08.031
|View full text |Cite
|
Sign up to set email alerts
|

The causal nexus between financial development and economic growth in Kenya

Abstract: This paper aims to reexamine the relationship between financial development and economic growth in Kenya over the period of 1971-2011. Since, financial sector plays a vital role in mobilizing and allocating savings into productive ventures, the core issue of this investigation remains important for developing economics. The examination is based on a Cobb-Douglas production augmented by incorporating financial development. A simulation based ARDL bounds testing and Gregory and Hansen's structural break cointegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 32 publications
2
94
1
1
Order By: Relevance
“…This is in line with the findings of Abu-Bader and Abu-Qarn (2008) who documented that no clear evidence exists to support the existence of any linkage between financial development proxy by M2 and economic growth for MENA economies. However, the findings contradict the results of Uddin et al (2013) who noted that a significant relationship existed between money supply as a percentage of RGDP and economic growth for Kenya. In terms of existence of a significant relationship, the results from our analysis contradict the findings of Odhiambo (2009) significant in the short run.…”
Section: Results Of the Long-run Relationshipcontrasting
confidence: 56%
See 1 more Smart Citation
“…This is in line with the findings of Abu-Bader and Abu-Qarn (2008) who documented that no clear evidence exists to support the existence of any linkage between financial development proxy by M2 and economic growth for MENA economies. However, the findings contradict the results of Uddin et al (2013) who noted that a significant relationship existed between money supply as a percentage of RGDP and economic growth for Kenya. In terms of existence of a significant relationship, the results from our analysis contradict the findings of Odhiambo (2009) significant in the short run.…”
Section: Results Of the Long-run Relationshipcontrasting
confidence: 56%
“…For instance, Uddin, Sjö, and Shahbaz (2013) used Cobb-Douglas production, simulation-based ARDL bound testing and Gregory and Hansen's structural break cointegration approaches to analysis data sourced from 1970 to 2011 on Kenya's economy and observed that in the long run, a positive relationship existed between financial development and economic growth. Their finding contradicts earlier work by Odhiambo (2009) who used Granger causality test and observed that money supply (M2) as a percentage of GDP exhibits a negative effect on economic growth for the same economy.…”
Section: Trade Openness and Economic Growth Nexusmentioning
confidence: 99%
“…However, the overall literature supports a positive effect of financial development on long-run economic growth. Examples of some recent studies that support the positive effect of financial development on economic growth include: Hassan (2003), Hassan et al (2011), Khoutem et al (2014) and Uddin et al (2013). Hsueh et al (2013) report that financial development stimulates economic growth in Asian countries including China.…”
Section: Economic Growth Financial Development and Trade Opennessmentioning
confidence: 99%
“…Then, this unit root test selects that time break which reduces the one-sided t-statistic to test c(=c-1)=1. Uddin et al (2013) suggested that conventional cointegration techniques do not provide reliable results when data are plagued with structural breaks. Therefore, this study…”
Section: Unit Root Testsmentioning
confidence: 99%